The use of linked activity schedules to teach children with autism to play hide‐and‐seek. Issue 3 (6th June 2014) - Brodhead, Matthew T.; Higbee, Thomas S.; Pollard, Joy S.; Akers, Jessica S.; Gerencser, Kristina R.
Abstract : Linked activity schedules were used to establish appropriate game play in children with autism during a game of hide‐and‐seek. All 6 participants demonstrated acquisition of appropriate play skills in the presence of the activity schedules and maintained responding during subsequent phases. When the schedules were removed, responding decreased to baseline levels, demonstrating that the schedules controlled responding. Implications for future research on the use of activity schedules to teach social behavior are discussed.